Increased Serum Level of Interleukin-10 Predicts Poor Survival and Early Recurrence in Patients With Peripheral T-Cell Lymphomas - Zhang, Yan; Zheng, Yanlong; Shou, Lihong; Shi, Yuanfei; Shen, Huafei; Zhu, Mingyu; Ye, Xiujin; Jin, Jie; Xie, Wanzhuo (Frontiers in Oncology, 2020)
Peripheral T cell lymphoma (PTCL) is an alloplasm group of aggressive and lymphoproliferative tumors with heterogeneous morphological changes of mature T cell immunophenotype. It has multiple subtypes and most of them have poor prognosis. Interleukin 10 (IL-10) is one kind of multi-cell-derived and multifunctional cytokine. It regulates the growth and differentiation of cells, participates in inflammation and immune response, plays an important role in tumor and infection, and is closely related to blood system diseases. Therefore, we implemented a retrospective study of 205 patients who were newly diagnosed with PTCL to explore the relationship between IL-10 and prognosis and early recurrence. We found patients with IL-10 ≥3.6 pg/ml achieved a lower CR rate and higher 1-year recurrence rate than patients with IL-10 <3.6 pg/ml (14.4 vs. 51.9%; 17.6 vs. 49.5%). On multivariate analysis, moreover, elevated IL-10 is an extremely important prognostic factor in PTCL, which can lead to worsening of overall survival (OS), low complete response (CR) rate and higher early relapse rate. Therefore, measurement of IL-10 levels in peripheral blood at the initial stage are useful for predicting the prognosis and helping us to make different treatment plans for individual patients. In the near future, IL-10 inhibitors or antagonists may become a new method of immunotargeting therapy for patients with PTCL.